PEMANFAATAN FERMENTASI REMPAH-REMPAH SEBAGAI CAMPURAN PAKAN LELE - Minto Minto (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2019)
The business of Catfish Farmers (PIL) has become increasingly restless because of the high price of catfish feed in the market. Seeing the progress that is progressing, the increasing number of PILs will bring new problems to thelocalgovernment.Moreover,whatisfacedinthePILproblemisthereducedqualityofcatfishfeed. The purpose of this study was to determine the proximate protein content by using a proximate test on catfish feedderivedfromspicefermentationcombinedwithpapayafruitandstarchaddedwithcanetreacle. A total of 9 compositions of spices used in this fermentation, turmeric 0.5 kg, laos 0.5 kg, key 0.5 kg, kencur 0.25 kg, temulawak 0.5 kg, molasses 0.5 kg, betel leaf 0 , 25 kg, temuireng 0.25 kg, ginger 0.25 kg and 0.5 kg blimbing, 1 kg papaya plus sugarcane drops 1.5 liter and IM4 0.5 kg. Seteleh milled the composition of fermented spices to produce 35 liters of fermented liquid, then added 40 liters. The liquid spice mixture is stored for15daysinavessel,the fermentationprocessofcatfishfeedbeforeconsumptiontakes1 day.Fromthe results ofthestudythatthecontentoffermentedproteinwithspicesofsugarcanedropsof31.39%withaconversionof 32.41%incatfishfeedcanincreaseproteinlevelsincatfishfeed.